Microenterprise Lending and Assistance Program (MELA): review, analysis and recommendations - Kelley, Brian; Pikholz, Lynn (© Shorebank Advisory Services, BRAC, 2016)
1. MELA loan portfolio trends (1996-199) 2. MELA repeat borrowers: a mystery 3. MELA portfolio analysis 4. MELA program recommendations.